2018
DOI: 10.48048/wjst.2019.5323
|View full text |Cite
|
Sign up to set email alerts
|

Productions and Functional Properties of Palm Sugars

Abstract: Sugar profile, antioxidant properties, DNA damages, and in vitro predicted glycaemic index (pGI) of palm sugars (syrup and powder) were investigated in comparison with refined cane sugar. It was found that palm sugars exhibited better nutritional qualities than refined cane sugars. Palm sugars in both syrup and powder forms showed similar results, except in some properties. They contained a high content of fructose and glucose. They also exhibited better antioxidant properties, as evidenced by the high content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…[10] believe it could be used as a natural sweetener. [11] also found that a blend of palm sugar and maize starch had a slower digestion rate and, as a result, a lower glycemic index value than refined cane sugar. This phenomenon suggests that palm sugar lowers the glycemic index of food goods.…”
Section: Introductionmentioning
confidence: 88%
“…[10] believe it could be used as a natural sweetener. [11] also found that a blend of palm sugar and maize starch had a slower digestion rate and, as a result, a lower glycemic index value than refined cane sugar. This phenomenon suggests that palm sugar lowers the glycemic index of food goods.…”
Section: Introductionmentioning
confidence: 88%
“…The cooking process will inhibit the fermentation of the sap so that it can maintain the sucrose levels in the sap. Srikaeo et al [34] reported that high temperatures in the sap could activate the invertase enzyme. The optimal activity of the invertase enzyme is in the temperature range of 25-60 o C [35] so that the invertase reaction in sucrose to reducing sugar can be reduced or inhibited.…”
Section: G Sucrose Levelsmentioning
confidence: 99%
“…It contains inulin, a dietary fiber that promotes good digestion through regulation of gut bacteria. Nutritional properties distinguish Palmyra palm jaggery from crude cane sugar; the former shows antioxidant properties as well [2]. It contains 1.04% protein, 0.19% fat, 76.86% sucrose, 1.66% glucose, 3.15% total minerals, 0.861 % calcium, 0.052% phosphorus; also 11.01 mg iron per 100 g and 0.767 mg of copper per 100 g. Fresh sap is reported to contain vitamin B complexes [3].…”
Section: Introductionmentioning
confidence: 99%